Micron-scale voltage and [Ca2+]i imaging in the intact heart - Lu, Xiao-long; Rubart, Michael (Frontiers in Physiology, 2014)
Studies in isolated cardiomyocytes have provided tremendous information at the cellular and molecular level concerning regulation of transmembrane voltage (Vm) and intracellular calcium ([Ca2+]i). The ability to use the information gleaned to gain insight into the function of ion channels and Ca2+ handling proteins in a more complex system, e. g., the intact heart, has remained a challenge. We have developed laser scanning fluorescence microscopy-based approaches to monitor, at the sub-cellular to multi-cellular level in the immobilized, Langendorff-perfused mouse heart, dynamic changes in [Ca2+]i and Vm. This article will review the use of single- or dual-photon laser scanning microscopy [Ca2+]i imaging in conjunction with transgenic reporter technology to a) interrogate the extent to which transplanted, donor-derived myocytes or cardiac stem cell-derived de novo myocytes are capable of forming a functional syncytium with the pre-existing myocardium, using entrainment of [Ca2+]i transients by the electrical activity of the recipient heart as a surrogate for electrical coupling, and b) characterize the Ca2+ handling phenotypes of cellular implants. Further, we will review the ability of laser scanning fluorescence microscopy in conjunction with a fast-response voltage-sensitive to resolve, on a subcellular level in Langendorff-perfused mouse hearts, Vm dynamics that typically occur during the course of a cardiac action potential. Specifically, the utility of this technique to measure microscopic-scale voltage gradients in the normal and diseased heart is discussed.